Sustainable boron removal from aqueous solutions using pomegranate peel adsorbents: A comprehensive study on isotherms, kinetics, and thermodynamics - Fawaz Al-Badaii; Khairiatul Mardiana Jansar; Nurul Ain Ab Jalil; Azhar Abdul Halim (Desalination and Water Treatment)
This study investigates the efficacy of pomegranate peel powders, specifically raw pomegranate peels (RPA), hydrochloric acid-modified (APA), and sodium hydroxide-modified (BPA) variants, as adsorbents for boron removal from aqueous solutions. Fourier-transform infrared (FTIR) analysis was employed to identify the functional groups involved in the adsorption process, while field emission scanning electron microscopy (FESEM) was utilized to examine the surface morphology of the adsorbents. Batch adsorption experiments optimized parameters such as pH, adsorbent dose, initial boron concentration, contact time, and temperature. The optimal pH for adsorption was 6, with maximum efficiencies of 42%, 69.3%, and 67.26% for RPA, APA, and BPA, respectively. Adsorption capacity increased with higher doses of adsorbents and temperature. The Langmuir model describes the adsorption isotherm well, while the adsorption kinetics were adequately described by the sequential fitting of the Elovich and pseudo-first-order models. Thermodynamic parameters (ΔS°, ΔG°, ΔH°) were examined during boron adsorption. A positive entropy change (∆S) indicated increased disorder. All adsorbents (RPA, APA, BPA) favoured boron, with APA and BPA showing a stronger affinity than RPA. Adsorption was endothermic and non-spontaneous, necessitating external energy. The study underscores the economical and reliable nature of RPA, APA, and BPA as effective adsorbents for repetitive boron ion removal, emphasizing their potential for sustainable water treatment solutions.